Multiculturalism Education for Refugees in Transit - Wahyuni, Dewi Sari; Bayu, Eka Pasca Surya (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
In non-formal classroom during their waiting time in transit, refugees often found it difficult to have dynamic teamwork with others from diverse sociocultural. Things considered small stuffs for some turned out to be a problematic issue to others. Their various background; home countries, ethnicities, previous socioeconomic status added to the exclusion and specific group connection with tendency of being unsettled when they were obligated to mix with their fellows outside their comfort group. Even though most of these people have experienced in moving around from one country into another, their marginal life was not a much of help to their socialization with people outside of their community. Promoting multicultural education which values diversity and includes the perspectives of a variety of cultural groups on a regular basis took longer time to decrease prejudice, tolerate changing habits and eliminate gender bias.